Terrorism and Integration of Muslim Immigrants - Ahmed Elsayed; Andries de Grip (Institute for the Study of Labor (IZA), 2013)
We study the effect that a series of fundamentalist-Islamic terrorist attacks in Europe had on the attitudes of Muslim immigrants in the Netherlands towards integration. Shortly after the attacks, Muslim immigrants' perceived integration, as measured by various indicators, decreased significantly relative to that of non-Muslims immigrants whereas there is no evidence for the existence of a negative trend in the integration of Muslims prior to the terrorist attacks. We further show that terrorism has a particularly negative impact on the integration of the highly educated, employed, and less religious Muslims - those who arguably have a strong potential for integration.
Keywords: F22; J15; Z13; 330; terrorism; integration; Muslim immigrants; Terrorismus; Meinung; Muslime; Migranten; Soziale Integration